2004
DOI: 10.1080/02656730400007212
|View full text |Cite
|
Sign up to set email alerts
|

MR-guided laser-induced thermotherapy (LITT) of liver tumours: experimental and clinical data

Abstract: MR-guided laser-induced interstitial thermotherapy (LITT) is a percutaneous, minimally invasive treatment modality for treating liver lesions/metastases, soft tissue tumours and musculoskeletal lesions. In this group, MR-guided LITT is currently performed under local anaesthesia on an out-patient basis with a specially designed saline-cooled laser application system. Nd:YAG laser (1064 nm wave length) was used for tumour ablation. Magnetic resonance imaging (MRI) using both open and closed MR units has proven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(78 citation statements)
references
References 16 publications
0
74
0
4
Order By: Relevance
“…Cryotherapy was the first method introduced in the treatment of liver metastases as an alternative to surgery [11]. Since then LITT [12,13] and RFA [14 Á16] were introduced and these are now the dominating methods for nonsurgical treatment of liver metastases. Local control rates in individual tumor based retrospective analysis of patients with a variety of tumor types treated by LITT or RFA are in the range 54 Á98%.…”
Section: Discussionmentioning
confidence: 99%
“…Cryotherapy was the first method introduced in the treatment of liver metastases as an alternative to surgery [11]. Since then LITT [12,13] and RFA [14 Á16] were introduced and these are now the dominating methods for nonsurgical treatment of liver metastases. Local control rates in individual tumor based retrospective analysis of patients with a variety of tumor types treated by LITT or RFA are in the range 54 Á98%.…”
Section: Discussionmentioning
confidence: 99%
“…Although both methods have been used in clinical studies of radiofrequency (RF) and microwave ablation, an optimal delivery method has not yet been determined (6)(7)(8)(9) (10). Four temperature probes were placed in a line bisecting an axis of symmetry beginning at the array center, with 1 cm spacing between probes (Fig 2).…”
Section: Implications For Patient Carementioning
confidence: 99%
“…Typically penetration in the range of 1-20 mm is sufficient for the ablation of cancer cells that are near the surface of the skin [160,191,193,204]. However, it has been reported that depths of 50-80 mm have been achieved [186,205]. Fig.…”
Section: Photothermal Ablation (Pta) Therapymentioning
confidence: 99%